Efisiensi Pertanian Jagung: Sosialisasi Dan Pendampingan Penggunaan Alat Tanaman Biji Jagung Untuk Meningkatkan Efisiensi Kerja Petani - Syahputra, Muhammad Reza; Jovian, Satrio Jiro; Oktaviano, Dion Ardian; Arif, Muhammad Junaidi; Diyanti, Daffa Dwi Sri (Yayasan Cendekia Gagayunan Indonesia, 2025)
Agricultural technology innovations continue to evolve to enhance efficiency and productivity. One such innovation is the 2-in-1 corn planting tool, which enables the simultaneous planting of two corn seeds in a single motion. This study aims to evaluate the tool's effectiveness in improving crop yields and labor efficiency. A qualitative case study approach was employed, involving interviews and direct observation of three farmers who tested the tool in Candiwatu Village. The findings show that the tool reduces planting time by 30–40%, lessens physical fatigue, and ensures consistent planting depth and spacing. Furthermore, it is environmentally friendly as it does not rely on external energy sources. Thus, the 2-in-1 corn planting tool is considered feasible for wider adoption as a simple mechanization solution in Indonesia's corn farming sector.